A domino Kornblum-DeLaMare/aza-Michael reaction of 3, 6-dihydro-1, 2-dioxines and application to the synthesis of the ceramide transport inhibitor (±)-HPA-12. Issue 12 (22nd March 2018) - Legendre, Sarah V.A.-M.; Jevric, Martyn; Klepp, Julian; Sumby, Christopher J.; Greatrex, Ben W.
Abstract: A Kornblum-DeLaMare/aza-Michael reaction of 3, 6-dihydro-1, 2-dioxines with primary and secondary amines has been developed which affords 4-hydroxy-3-aminoketones. The aza-Michael products were reduced using non-selective NaBH4 /MeOH or diastereoselective (up to 92:8) SnCl4 /NaBH4 conditions yielding (1 R ∗, 3 S ∗ )-3-amino-1, 4-diols in up to 97% and 70% yield respectively. The major reduction product was converted in two steps to (±)-HPA-12, which is an inhibitor of the cytosolic ceramide transporting protein. Graphical abstract: